DINAMIKA PSIKOLOGIS EKS PECANDU NARKOBA: STUDI KASUS DI PUSAT REHABILITASI ODGJ WELAS ASIH INDONESIA WARAS MINISTRY, SERANG-BANTEN - Qoqom Komariah; Yahdinil Firda Nadirah (STKIP Subang, 2025)
Drug abuse constitutes a form of behavioral disorder that has serious implications for an individual’s mental health. This study aims to explore the psychological dynamics experienced by former drug users during their period of substance use and throughout the rehabilitation process. A qualitative approach using a case study method was employed with one patient undergoing rehabilitation at the Welas Asih Indonesia Waras Ministry Center for Mental Health Rehabilitation (Pusat Rehabilitasi ODGJ), Serang, Banten. Data were collected through semi-structured interviews and non-participatory observations. The findings indicate that the subject experienced severe psychological disturbances, including paranoia, delusions, auditory hallucinations, anxiety, and suicidal ideation during the period of drug use. Throughout the rehabilitation process, the subject demonstrated positive developments in self-acceptance, emotional regulation, and coping abilities through Cognitive Behavioral Therapy (CBT), individual counseling, meditation, and social support within the rehabilitation environment. These findings underscore the importance of a holistic, empathetic, and continuous psychological approach in supporting the recovery process of former drug addicts.